Literasi Demokrasi bagi Petani dan Nelayan melalui Sosialisasi Pilkada Kabupaten Pangandaran 2024 - Lisnarini, Naurah; Ariadne Shinta Dewi, Evie; Gemiharto, Ilham; Ikhwan Aji Sabda, Galang (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This community service project aims to evaluate the improvement in public understanding related to the 2024 Regional Head Election (Pilkada) socialization program, focusing on enhancing democratic literacy in Pangandaran Regency. The participants of this program consist of farmers and fishermen as voter groups. The program involves two speakers, a practitioner and an academician, in collaboration with the Pangandaran General Election Commission (KPU), with materials designed to improve public understanding of participation in the upcoming elections. Through the analysis of pre-test and post-test data given to 50 participants, the results show a significant increase in democratic literacy. These findings indicate that the socialization program has been effective in enhancing public understanding of democracy, particularly regarding the 2024 Pilkada. Overall, this activity emphasizes the importance of political socialization to strengthen public participation and improve the quality of future elections.